Deficiência de ferro: Conseqüências biológicas e propostas de prevenção - Umbelino, D. C. [UNESP]; Rossi, Elizeu Antonio [UNESP] (My University, 2006)
Iron deficiency is the commonest nutritional deficiency in the world. Although it affects adults, particularly women of reproductive age and during gestation, the most vulnerable group is children under two years of age. It affects mainly people living in developing countries, who have less access to balanced diets and health services and are exposed to precarious sanitary conditions. Iron deficiency has an impact on the immunity, adult work capacity and the cognitive development of children. Combating and preventing iron deficiency is one of the priorities in promoting public health. The strategies to achieve this end include the evaluation and correction of iron deficiency in pregnant women, the encouragement of breast feeding, oral iron supplementation in premature and newborn babies of low birth-weight, food enrichment and mobilization of the community.
Iron deficiency: Biological consequences and prevention strategies
Keywords: Adverse effects; Anemia; Iron deficiency; Prevention; iron; biology; breast feeding; clinical evaluation; cognitive development; community; developing country; diet; food; health promotion; health service; human; hygiene; immunity; iron deficiency; iron therapy; low birth weight; nutritional deficiency; pregnancy; pregnant woman; prematurity; public health; review; vulnerable population; work capacity